2y+9=3-y

Simple and best practice solution for 2y+9=3-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+9=3-y equation:



2y+9=3-y
We move all terms to the left:
2y+9-(3-y)=0
We add all the numbers together, and all the variables
2y-(-1y+3)+9=0
We get rid of parentheses
2y+1y-3+9=0
We add all the numbers together, and all the variables
3y+6=0
We move all terms containing y to the left, all other terms to the right
3y=-6
y=-6/3
y=-2

See similar equations:

| −4x−1=−53 | | -2s+-9=1 | | -7k+8=-10-4k | | d+-10=-2 | | 3x+2+x=110 | | 8b-1=10b+3 | | 8.50+2x=50.50 | | 11+10x=71 | | 2s-2=18 | | 2+5q=q+8q-10 | | 3/q=9/63 | | 7x-4(2x+5)=3(5x+2)-6+4x | | 9k+–9k+–17k−–7k−–11k=–14 | | -3k=3 | | −1=−5x−16 | | -6g+10=7g-3 | | .8(x-2)=1.067 | | w-1=14 | | 32=2x+1 | | 1.03+1.91x=7.06 | | .8(x-2)=1.066666 | | x/3−5=3 | | 15.75m+.05=16.53m+.13 | | 1.3x=5,000 | | x3−5=3 | | 8x2-16x-10=0 | | x2–43x=0 | | 2^1/3c=2^1/10 | | 5b+8=-10+7b | | 3x15=1 | | 3(3-h)-6=-5h | | 4x–16=3x–4–3x |

Equations solver categories